Chemistry and technology of cereals as food and feed - Samuel A Matz (New Delhi MEDTECH, 2019)
The first edition of this book was published in 1959. It was one of the first two or three books produced by Dr. Donald K. Tressler when he retired as Scientific Director of The Quartermaster Food and Container institute for the Armed Forces and took over the AVI Publishing Co. I later wrote or edited eleven more book manuscripts for AVI, but I never got around to preparing a second edition of The Chemistry and Technology of Cereals as Food and Feed. The original book can still be found, after 30 odd years, in food technology libraries all over the world, though many of the copies are in a sorry condition by now. There have been numerous requests for a modernized version of (3z(BThe Chemistry and Technology of Cereals as Food and Feed.(3y (BSince there seems to be no other book that covers this broad field at the same technical level. With considerable misgivings based on the magnitude of the task, I decided to undertake this project and have spent the last two years in developing the manuscript which forms the basis of the book you are now reading.s
Keywords: Technology